Association of a modified body shape index with cognitive impairment in middle-aged and elderly Chinese adults: a cross-sectional analysis from CHARLS - Guotao Liu; Qiong Xu; Suhua Zhang; Jianyuan Zhang; Jianyuan Zhang (Frontiers in Nutrition)
PurposeThis study aimed to investigate the association between A Body Shape Index (ABSI) and cognitive impairment in middle-aged and elderly Chinese adults.Patients and methodsWe analyzed baseline data from the 2011 China Health and Retirement Longitudinal Study (CHARLS), including 6,762 participants aged ≥45 years. The modified ABSI of adults in China was calculated using waist circumference (WC), body mass index (BMI), and height. Cognitive function was assessed through episodic memory and cognitive status tests, with impairment defined as a composite score ≤11. Multivariate logistic regression, fitted smoothing curves, and subgroup analysis were employed to evaluate the associations and interactions. Receiver operating characteristic (ROC) curves were used to compare the diagnostic performance of ABSI, BMI, and WC.ResultsAfter full adjustment, each 0.01-unit ABSI increase conferred a 45.7% higher risk of cognitive impairment (odds ratio [OR] = 1.457). Participants in the highest ABSI quartile had a 48.3% higher risk compared to the lowest quartile (p for trend < 0.001). Dose–response analysis revealed a positive relationship (p < 0.001) between ABSI and cognitive impairment. ABSI demonstrated superior diagnostic accuracy (Area Under the Curve [AUC] = 0.603) compared to BMI (AUC = 0.570) and WC (AUC = 0.548).ConclusionElevated ABSI independently predicts cognitive impairment in Chinese middle-aged and older adults. ABSI demonstrates better diagnostic accuracy compared to BMI and WC. These findings highlight ABSI’s utility as a cost-effective anthropometric tool for cognitive risk stratification in aging populations.